Energy-Efficient Wireless Body Area Networks for Healthcare - Navya Padma Priya (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Recent developments and advancements in information and communication technology enhance several aspects of life. Significantly, the healthcare business has increasingly integrated information and communication technology-based services. One of the most crucial services is the monitoring of distant patients, which allows healthcare experts to watch, diagnose, and prescribe treatment without physical presence. The benefit of sensor technology downsizing allows for installation in, on, or off the patient’s body, enabling the wireless transmission of physiological data to distant servers. This technology is referred to as a Wireless Body Area Network (WBAN). This article illustrates the architecture of WBAN, the communication technologies used in WBAN, as well as the problems and other factors associated with WBAN. This article delineates the architectural constraints of current WBAN communication systems. azure Moreover, implementation specifications are delineated in accordance with the IEEE 802.15.6 standard. Ultimately, this serves as a motivational impetus for the future advancement of research integrating Software Defined Networking (SDN), Energy Harvesting (EH), and Blockchain technology into Wireless Body Area Networks (WBAN).